Organizational monitoring and reflex of suffacation of work . An opinions study of sample workers in manufacturing of Isphelt dohuk - خليف نوفل, سلطان احمد; سليمان رشيد, نضال علي (Journal of Economics and Administrative Sciences, 2019)
The study aims to determine the organizational monitoring mechanism in target organization as well as knowing the suffocation of work. The study depends on a questionnaire as a tool of collecting data on distributed random sample involved (45) person from different   levels in manufacturing isphelt Dohuk. The study depends on some hypothesis, the most significant one is that there is not impact of organizational monitoring of suffocation especially on the target organization.